THE TRANSFORMATION STRATEGY AND SAFETY IMPLEMENTATION OF CULTURE CHANGE AT PT PERTAMINA DRILLING SERVICES INDONESIA - Muhammad Arifin; Chaerudin Chaerudin (Dinasti Publisher, 2020)
This research had purposed to analyzed those Transformation Strategy and Safety Implementation of Culture Change in improving the Occupational Safety and Health from PT Pertamina Drilling Services Indonesia during period 2015-2020. These research data was result from in-dehpt, interview, FGD, primary and secondary data from PT Pertamina Drilling Services Indonesia during these implementation of HSE Work culture change program during period of 2015-2020. Research method used qualitative with type of case study research. Data analysis used Mckensy 7S Framework and The results showed that PT Pertamina Drilling Services Indonesia has a strategic plan for any kind of transformation from HSE Work culture until 2030 through